2020
DOI: 10.3390/publications8010013
|View full text |Cite
|
Sign up to set email alerts
|

International Collaboration in Open Access Publications: How Income Shapes International Collaboration

Abstract: Does the rise of open access journals change the way researchers collaborate? Specifically, since publishing in open access journals requires a publication fee, does income affect how researchers form international collaborations? To answer this question, we create a new data set by scraping bibliographic data from Multidisciplinary Digital Publishing Institute (MDPI) journals. Using the four income group classifications from the World Bank Analytical Classifications, we find that researchers from low-income n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…APCs may also have an impact on how authors create co‐authorship networks. Using Multidisciplinary Digital Publishing Institute (MDPI) journals as a case study, Cary and Rockwell (2020) found that researchers from low‐income countries were more likely to form international collaborations than researchers from wealthier nations, possibly to cover the costs of APCs.…”
Section: The Transition From Journal Subscriptions To Oa Publishing B...mentioning
confidence: 99%
“…APCs may also have an impact on how authors create co‐authorship networks. Using Multidisciplinary Digital Publishing Institute (MDPI) journals as a case study, Cary and Rockwell (2020) found that researchers from low‐income countries were more likely to form international collaborations than researchers from wealthier nations, possibly to cover the costs of APCs.…”
Section: The Transition From Journal Subscriptions To Oa Publishing B...mentioning
confidence: 99%
“…Since the start of the 21 st century, the scientific community has witnessed an unprecedented popularity of the Open Access (OA) movement (Björk, 2004;Chen-Chi, 2006;Sotudeh and Estakhr, 2018). A successful transition into an OA publishing model is seen as a good way to ensure better dissemination of knowledge and more equity between researchers, especially for those from institutions in low-income countries faced with the issue of paying subscription fees (Prosser, 2003;Tananbaum, 2003;Solomon and Björk, 2012;Cary and Rockwell, 2020). However, OA does not necessarily mean "free", and raises the question of the business model underlying scientific publishing.…”
Section: Introductionmentioning
confidence: 99%
“…The Asian country Taiwan has collaborated with Norway and Turkey, and Australia with Saudi Arabia. These networks indicate the economic and cultural differentiation in the global pattern [31].…”
Section: Mapping Of Countriesmentioning
confidence: 99%